Functional fitness and psychological well-being in older adults - Eliza E. Tóth; Aleksandar Vujić; Ferenc Ihász; Roberto Ruíz-Barquín; Attila Szabo (BMC Geriatrics)
Abstract Background Physical fitness and functioning are related to better mental health in older age. However, which fitness components (body composition, strength, flexibility, coordination, and endurance) are more closely related to psychological well-being (PWB) is unclear. Methods This research examined how body mass index (BMI) and six indices of functional fitness (i.e., lower and upper body strength, lower and upper body flexibility, coordination [based on agility and balance], and aerobic endurance) relate to five psychological measures that could mirror PWB (i.e., resilience, mental well-being, optimism, life satisfaction, and happiness). Thirty-nine older adults (60–94 years; two-thirds female) were examined with the Fullerton Functional Fitness Test (FFFT) after completing five psychometric instruments. Results Data were analyzed with correlations, ordinary least squares regressions, and regularized (elastic net) regressions, calculating the Lindeman, Merenda, and Gold (LMG) indices of the relative importance of the six FFFT components separately for the five psychological measures. Results revealed that BMI, upper body strength, and upper body flexibility were the least significant predictors of PWB. In contrast, endurance, complex movement coordination, and lower body flexibility emerged as the most significant predictors. Still, lower body strength correlated moderately positively with all PWB indices, and similarly, upper body flexibility with resilience, mental well-being, and happiness. Conclusions These findings should stimulate research on the mechanism connecting functional fitness with PWB in older adults. Further, apart from their novelty, the findings could be valuable in providing directions for physical fitness intervention programs targeting mental and physical health for older people.